2016
DOI: 10.1371/journal.pone.0159192
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Protects Gamma Oscillations by Inhibiting Hippocampal LTD

Abstract: NMDA receptors have been widely reported to be involved in the regulation of synaptic plasticity through effects on long-term potentiation (LTP) and long-term depression (LTD). LTP and LTD have been implicated in learning and memory processes. Besides synaptic plasticity, it is known that the phenomenon of gamma oscillations is critical in cognitive functions. Synaptic plasticity has been widely studied, however it is still not clear, to what degree synaptic plasticity regulates the oscillations of neuronal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…An alternative explanation is that g oscillatory activity not only has an effect on LTP-like phenomena, but also modulates the physiological mechanisms responsible for LTD-like plasticity. This hypothesis is supported by recent evidence from animal and human studies [15,46]. Huang and colleagues [46] demonstrated that N-methyl-Daspartate (NMDA)-induced LTD produces a reduction of g oscillatory activity in mouse cortex.…”
Section: Discussionmentioning
confidence: 79%
“…An alternative explanation is that g oscillatory activity not only has an effect on LTP-like phenomena, but also modulates the physiological mechanisms responsible for LTD-like plasticity. This hypothesis is supported by recent evidence from animal and human studies [15,46]. Huang and colleagues [46] demonstrated that N-methyl-Daspartate (NMDA)-induced LTD produces a reduction of g oscillatory activity in mouse cortex.…”
Section: Discussionmentioning
confidence: 79%
“…Due to the low intensity of the stimulation, we may speculate that alternating currents reached the more external layer of cerebellum where Purkinje cells have their bodies [41]. By modulating the activity of these cells in the cerebellar cortex, gamma-tACS might have prevented the LTD processes needed for the formation of internal models and consequently for sequence learning [42,43]. Indeed, inducing gamma oscillations might have led to long-term potentiation (LTP) [44].…”
Section: Discussionmentioning
confidence: 99%
“…e Average total distance travelled in the OFT for saline and (2R,6R)-HNK treated WKY rats (n = 6/group) at 30 min or 24 h post-injection, where HNK had no effects on WKY general locomotor activity. *p ≤ 0.05, **p ≤ 0.01, ***p ≤ 0.001 51,54], effects which seem to be in line with ketamine's action as an open-channel NMDAR antagonist. However, importantly, others have previously no change [49,50] or even a facilitation of LTP [55][56][57] in the rodent HPC following ketamine.…”
Section: Discussionmentioning
confidence: 55%